Pengaruh Pola Asuh Orang Tua, Pemenuhan Asi Ekslusif dan Sanitasi Lingkungan terhadap Status Gizi Balita di Posyandu Desa Wilamaci - Nurul Hidayah; M. Noris; Juraidin; Darmin (Lembaga Bale Literasi, 2026)
This study aims to analyze the effects of parenting styles, exclusive breastfeeding, and environmental sanitation on the nutritional status of toddlers at the Wilamaci Village Posyandu in Monta Subdistrict, Bima Regency. This study employed a quantitative method with an analytical observational approach and a cross-sectional design. The study sample consisted of 51 mothers of toddlers at the Wilamaci Village Posyandu, selected using simple random sampling. Data were collected through face-to-face interviews and questionnaires, and the data were analyzed using Pearson’s correlation test and the chi-square test. The results of the study showed that the nutritional status of toddlers consisted of 20 toddlers (39.2%) in the normal category, 9 toddlers (17.6%) in the stunted category, and 22 toddlers (43.1%) in the severely stunted category. Based on the correlation test results, only the exclusive breastfeeding indicator had a significant relationship with the nutritional status of toddlers (r = -0.279; p = 0.048). Meanwhile, parenting practices and environmental sanitation did not show a significant relationship because their p-values were greater than 0.05 (p > 0.05). In terms of respondent characteristics, the majority of mothers were aged 26-30 years (70.6%), had completed high school (70.6%), and were homemakers (92.2%). This study concludes that exclusive breastfeeding is the most dominant factor associated with the nutritional status of toddlers at the Wilamaci Village Posyandu. Therefore, it is necessary to strengthen education on the benefits of exclusive breastfeeding, the implementation of responsive parenting practices, and good environmental sanitation practices through Posyandu activities and cross-sectoral collaboration